OPTIMIZATION OF THE SOLID FUEL COMBUSTION PROCESS IN COMBUSTION CHAMBERS IN ORDER TO REDUCE HARMFUL EMISSIONS - P. Safarik; A.S. Askarova; S.A. Bolegenova; V.Yu. Maximov; A.O. Nugymanova (Academic Scientific Journal of Computer Science, 2019)
The methods of numerical simulation are used to study the processes of heat and mass transfer in the combustion chamber of an operating coal-burning Kazakhstan thermal power plant. Computational experiments were performed on the combustion of high-ash Karaganda coal in the combustion chamber of the BKZ-75 boiler (Shakhtinsk, Karaganda region). As a result of numerical simulation of the combustion processes, the distributions of the total velocity vector, temperature fields, concentration fields of nitrogen oxides NO over the entire volume of the combustion chamber and at its exit were obtained. A comparative analysis of the characteristics of heat and mass transfer processes for the two studied modes of supplying fuel to the combustion chamber through burner devices is given for the direct-flow method of supplying the mixture when the burners are located on opposite side walls and the vortex method of supplying the mixture when the burners are installed at a 30-degree angle from the center of symmetry of the boiler. It is shown that the vortex method of supplying air mixtures allows optimizing the combustion of high-ash coal, since in this case there is an increase in temperature in the core of the torch and a decrease in it at the exit from the combustion chamber, which has a significant effect on the chemical processes of the formation of combustion products. The average value of the concentration of nitrogen oxide NO at the outlet of the combustion chamber decreases when using burner devices with a swirl of the mixture flow and conforms to norms the maximum permissible concentration.